2022
DOI: 10.1186/s12974-022-02525-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in the anterior cingulate cortex: the potential supraspinal mechanism underlying the mirror-image pain following motor fiber injury

Abstract: Background Peripheral nerve inflammation or lesion can affect contralateral healthy structures, and thus result in mirror-image pain. Supraspinal structures play important roles in the occurrence of mirror pain. The anterior cingulate cortex (ACC) is a first-order cortical region that responds to painful stimuli. In the present study, we systematically investigate and compare the neuroimmune changes in the bilateral ACC region using unilateral- (spared nerve injury, SNI) and mirror-(L5 ventral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 105 publications
1
9
0
Order By: Relevance
“…Consistent with our previous findings [ 34 , 45 ], unilateral SNI induced a significant decrease in ipsilateral paw withdrawal thresholds in the present study, indicating that the neuropathic pain model was successfully duplicated. Next, we compared the bilateral expression of ACC Piezo1 between SNI and sham rat groups and found that SNI significantly increased the level of Piezo1 on both sides at PO day 7 ( Figure 1 A; p -value < 0.05 ipsilaterally, p -value < 0.01 contralaterally).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with our previous findings [ 34 , 45 ], unilateral SNI induced a significant decrease in ipsilateral paw withdrawal thresholds in the present study, indicating that the neuropathic pain model was successfully duplicated. Next, we compared the bilateral expression of ACC Piezo1 between SNI and sham rat groups and found that SNI significantly increased the level of Piezo1 on both sides at PO day 7 ( Figure 1 A; p -value < 0.05 ipsilaterally, p -value < 0.01 contralaterally).…”
Section: Resultssupporting
confidence: 93%
“…Abnormally high Ca 2+ influx also leads to the instability and unwinding of axonal cytoskeletal transport mechanisms, ultimately leading to irreversible neurodegeneration [ 75 , 76 ]. Therefore, the disturbance of the immune cytokine microenvironment in the ACC after SNI [ 34 , 45 ] is likely to cause abnormal Piezo1 expression and, thereby, contribute to neuropathic pain. In the present study, we found that the expression of Piezo1 mechanical channels was specifically increased in ACC PV-INs after SNI ( Figure 1 and Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations